2019
DOI: 10.1111/jocd.13183
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of anti‐inflammatory moisturizer vs hydrophilic cream in elderly patients with moderate to severe xerosis: A split site, triple‐blinded, randomized, controlled trial

Abstract: Background: Xerosis is a common problem among the elderly, characterized by dryscaling erythema, fissuring, or pruritus, which could be treated by anti-inflammatory moisturizers without side effects of steroids. Aims:We aimed to investigate the efficacy of anti-inflammatory moisturizer (MAS062D lotion) vs hydrophilic cream for the improvement of dry and barrier function skin in xerosis patients. Methods:A split site, triple-blinded, randomized, controlled trial was conducted in the elderly with moderate to sev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Xerosis, also known as dry skin, xeroderma, or xerosis cutis, is determined by structural and functional changes in keratinocytes due to an imbalance between hydrophilic and lypophilic content [ 79 ]. Generally, there is a decrease in water and lipid components in the stratum corneum, and consequently a decrease in stratum corneum hydration and an increase in TEWL [ 80 ]. The symptoms of this very common dermatological condition include pruritus and a feeling of tightness.…”
Section: Discussionmentioning
confidence: 99%
“…Xerosis, also known as dry skin, xeroderma, or xerosis cutis, is determined by structural and functional changes in keratinocytes due to an imbalance between hydrophilic and lypophilic content [ 79 ]. Generally, there is a decrease in water and lipid components in the stratum corneum, and consequently a decrease in stratum corneum hydration and an increase in TEWL [ 80 ]. The symptoms of this very common dermatological condition include pruritus and a feeling of tightness.…”
Section: Discussionmentioning
confidence: 99%
“…Comments : Many studies of moisturizers containing different moisturizing components involving elderly patients with asteatosis were conducted. Moisturizers containing heparinoids, 66–68 urea, 67,69 ceramide, 70 glycerol, 46 urea/ceramide NP/lactate, 71 diethylene glycol/dilinoleic copolymer, 72 glyceryl glucoside/natural moisturizing factors, 73 or vitis vinifera, vitamin C, vitamin E, telmesteine, hyaluronic acid, glycyrrhetinic acid, and shea butter 74 significantly reduced clinical findings of asteatosis and pruritus, improving the stratum corneum function (stratum corneum water content, TEWL, pH) in comparison with a control drug/base, untreated group, or state before administration. A systematic review of moisturizers for asteatosis in the elderly also concluded that moisturizers significantly reduced dry skin 75 .…”
Section: Cq1 Are Moisturizers Useful For Treating Age‐related Asteato...mentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11] In severe cases, topical steroids and antihistamines may be needed in addition to moisturisers. 12 Recognition of the physiological changes to the skin caused by ageing has gained importance in recent years due to an increasing population of older individuals. To the best of our knowledge, no study has measured the knowledge level of older people regarding skin dryness and the use of moisturisers.…”
Section: Introductionmentioning
confidence: 99%
“…Regular skin moisturising is very useful for delaying skin ageing and is also the most important step in the treatment of xerosis 1‐11 . In severe cases, topical steroids and antihistamines may be needed in addition to moisturisers 12 . Recognition of the physiological changes to the skin caused by ageing has gained importance in recent years due to an increasing population of older individuals.…”
Section: Introductionmentioning
confidence: 99%